Irradiação da luz violeta associada ao peróxido de carbamida para clareamento dentário em consultório: uma revisão sistemática e meta-análise - Bessa, Mariana Silva de (2024)
Introduction: Violet light irradiation has been proposed to enhance the in-office bleaching effect of carbamide peroxide. However, a systematic review and meta-analysis are needed to summarize the evidence and guide clinical recommendations. The objective of this study was to evaluate, through a systematic review and meta-analysis, whether inoffice irradiation of carbamide peroxide with violet light can improve the effect of tooth whitening without increasing sensitivity. Methodology: The searches for studies were conducted in the databases PubMed, Embase, Scopus, Web of Science and Google Scholar. Two independent and calibrated examiners (Kappa: 0.88) performed all systematic steps according to the PRISMA protocol. To assess the risk of bias, the RoB 2 tool was used. GRADE was used to analyze the certainty of evidence. Meta-analysis was performed using RevMan 5.4 software to evaluate tooth color change and tooth sensitivity to bleaching. The former was assessed by mean difference and the latter by risk difference. Results: Three randomized clinical trials were included. A statistically significant difference was found for color change favoring the application of violet light combined with carbamide peroxide (MD, 3.35; 95% CI, 0.80, 5.89), while no difference between groups was found for tooth sensitivity to bleaching (RD, 0.09; 95% CI, -0.03, 0.21). Conclusion: Violet light irradiation enhanced the in-office bleaching effect of carbamide peroxide without increasing sensitivity. However, the results regarding bleaching sensitivity should be interpreted with caution due to the moderate certainty of the evidence.